Agency for Whom and To What Ends: A Plan for Investigating Impacts of Agentic AI in Computing Education - Mak, Janice; Clear, Tony; Zhu, Tingting; Clear, Alison; Andrei, Oana; Goodfellow, Martin; Imbulpitiya, Asanthika; Oladapo, Elizabeth; Padiyath, Aadarsh; Pow-Sang, Jose Antonio; Williams, Rebecca (ACM, 2026)
Agentic AI, where AI systems have their own forms of agency, will present some of the most critical challenges that computing education will face, including regulatory gaps and amplified cascading social and ethical impacts. This working group proposes a landscape analysis of the ethical and societal implications of using Agentic AI in higher computing education. By exploring emerging literature and use cases of Agentic AI, we aim to contribute a timely landscape study exploring 1) the emerging challenges and opportunities associated with Agentic AI, 2) how higher education is beginning to adopt and use Agentic AI and the resulting ethical and societal impacts, and 3) the implications (e.g. challenges, opportunities, limitations) of integrating Agentic AI in computing education. The expected outputs are: 1) a protocol and literature scoping review of Agentic AI in education, and 2) an analysis of current practices and use cases in computing education. Together, these outputs aim to identify emerging patterns, use cases, key challenges, and principles to support the ethical and responsible integration of Agentic AI in education.